ChemInform Abstract: A Concise Formal Synthesis of (‐)‐Hamigeran B (XIV). Issue 28 (21st June 2013) - Jiang, Biao; Li, Ming‐ming; Xing, Ping; Huang, Zuo‐gang
Abstract The sequence starts with the synthesis of cyclopentenone (IV) by intermolecular Pauson—Khand reaction of (I) with an excess of Me2S as promoter.